2018
DOI: 10.1007/s10006-018-0712-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma rich in growth factors (PRGF) for the promotion of bone cell proliferation and tissue regeneration

Abstract: Human osteoblasts are driven to colonize PRGFs with a greater efficacy than negative controls, probably due to the presence of chemokines and growth factors in PRGFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Plasma rich in growth factors (PRGF) is an autologous scaffold that is obtained by platelet activation and fibrinogen polymerization. Several studies have shown the capacity of this preparation to stimulate collagen production, angiogenesis and cell differentiation, and anti-inflammatory and antibacterial properties have also been reported for PRGF [8][9][10]. Okada et al (2016) proved that PRGF induces matrix mineralization, accelerating its formation, and their work showed that TGF-β, PDGF-αβ, PDGF-ββ, and VEGF concentrations in supernatant were about 50% less than in rich fraction of PRGF [11].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Plasma rich in growth factors (PRGF) is an autologous scaffold that is obtained by platelet activation and fibrinogen polymerization. Several studies have shown the capacity of this preparation to stimulate collagen production, angiogenesis and cell differentiation, and anti-inflammatory and antibacterial properties have also been reported for PRGF [8][9][10]. Okada et al (2016) proved that PRGF induces matrix mineralization, accelerating its formation, and their work showed that TGF-β, PDGF-αβ, PDGF-ββ, and VEGF concentrations in supernatant were about 50% less than in rich fraction of PRGF [11].…”
Section: Introductionmentioning
confidence: 92%
“…Plasma rich in growth factors (PRGF) is an autologous scaffold that is obtained by platelet activation and fibrinogen polymerization. Several studies have shown the capacity of this preparation to stimulate collagen production, angiogenesis and cell differentiation, and anti-inflammatory and antibacterial properties have also been reported for PRGF [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblast culture was carried out according to previous literature [16][17][18]20]. Primary alveolar osteoblasts were obtained from the mandible of one healthy 60-year-old female donor during implant surgery, after signing pertinent informed consent.…”
Section: Osteoblast Proliferation Comparativementioning
confidence: 99%
“…The effect of APCs on soft tissues and periodontal ligament cells has been extensively studied, but the literature comparing the effect of GFs release kinetics between L-PRF and PRGF in osteoblast cultures is limited [12][13][14][15]. Previous studies focus on the effect of a single protocol on osteoblasts and very little research compares different APC protocols [16][17][18][19]. The aims of the present study were to characterize the controlled release of PDGF, VEGF, IGF-I and IL-1β from the fibrin matrix of PRGF and L-PRF as well as to evaluate their biological implication in osteoblasts, in terms of cell proliferation, alkaline phosphatase (ALP) activity, collagen-I biosynthesis and interleukin 6 (IL-6) release.…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal periosteal incisions are not provided, the soft tissues can be mobilized with the Soft Brushing Technique (J. Choukroun), disorganizing the periosteal collagen fiber as the brush tools don't cut anything avoiding conventional flap: the aim is to decrease the tension and increase the release of the tissues, which have as more as possible to cover the new graft volume. PTFE membrane should be inserted first in lingual/palatal site, since usually is simpler; a bone graft must be fit in place, obtaining it by heterologous bone mixed with A-PRF (cut into small pieces) and solidifying with PRGF 10,11,12,13 , very handy and stable to be positioned in desired volume, overcompensating by 2-3mm. Then the membrane is curved over the graft and placed to cover whole vestibular dimension; it is very important that the membrane does not touch adjacent teeth, leaving almost 1-2mm from dental surface.…”
Section: Protocolmentioning
confidence: 99%